(untitled) (Journal of the College of Basic Education, 2023)
A field study aimed at evaluating patients’ information about the causes of asthma. The research sample included (70) patients with asthma who were randomly selected from patients attending the consulting clinic of Baghdad Teaching Hospital for the period from 1/4/2011 to 1/9/2011.Information was collected by interviewing and answering the questionnaire prepared by the researcher, and the frequency distribution, percentage, and chi-square were used to analyze the data. The results were as follows: The highest percentage of the sample was males (52’9%) within the age group (21-30), and (34.3%) of them were high school diploma holders, and (60%) of the sample practiced the habit of smoking inside the house. The results also showed that the injury of one of the parents (6’58%) is evidence of the injury of one of the children with asthma, and that the winter season has a significant relationship to the increase in asthma attacks, as the rate was recorded (75.7%), while the rate was recorded (9.62%), that Exposure to animal hair does not affect the occurrence of asthma, and the results showed that there is no good significant relationship between the educational level of the patients and their knowledge of the causes of asthma, as the chi-square was recorded (8 44.5), while the scientific sources indicated that the educational level had a significant impact on reducing asthma .The study recommended the need to provide health awareness to the community about the factors affecting the occurrence of asthma and the harms of smoking inside the home, and the need to conduct a field study on a larger sample.